Achlya spiralis, a new aquatic oomycete with bent oogonial stalks, isolated from the Burgundian region of France - Paul, Bernard (2008)
Achlya spiralis sp. nov. was isolated from water samples collected in the river Tille in the Burgundian region of France. The new oomycete is described, illustrated and compared with related species of the genus Achlya. It is characterized by the presence of smooth-walled oogonia that are usually borne on bent or twisted oogonial stalks; mainly monoclinous, androgynous and diclinous antheridial branches and eccentric oospores which generally do not mature or mature after a long period of time. The internal transcribed spacer (ITS) region of its rRNA is comprised of 671 bases. The taxonomic description of this new species, its comparison with related oomycetes and the sequence of the ITS region of its rRNA are discussed here.